Contamination du lait cru et de l’attiéké vendus sur les marchés informels à Abidjan (Côte d’Ivoire) par le groupe Bacillus cereus et analyse des risques - Yobouet, B.A. (Université Nangui Abrogoua, 2016)
ABSTRACT IN ENGLISH In Côte d’Ivoire, although milk and attiéké play an important role in human nutrition, they could represent a poisoning risk to the consumer, due to poor hygiene throughout the production chain. This study aimed to contribute to the poisoning risk reduction linked to the consumption of local raw milk and attiéké contaminated with B. cereus group. For this, milk and attiéké production systems from farm to retail in Abidjan were studied. The risk of foodborne illness associated with the consumption of milk and attiéké was assessed using a questionnaire with 188 consumers of milk and 360 consumers of attiéké, respectively. On the one hand, 320 samples from the farms including 150 milk samples and on the other hand 16 samples of freshly prepared attiéké and 306 samples attiéké sold on the informal markets were collected and analyzed according to EN ISO 7932: 2004. The isolates were identified by polymerase chain reaction (PCR) and characterized by toxigenic and antibiotypic. In addition, the resistance of B. cereus group spores to hydrothermal warm up of attiéké was evaluated. The results showed that B. cereus group was found in 41.2% of milk of the samples taken from seller’s pooled milk with a mean load of 2.9 ± 1.0 log (CFU/mL). The prevalence of B. cereus group in attiéké samples taken from the informal markets was 25.2% and an average load of vegetative cells and spores were 2.4 ± 1.1 log (CFU/g) and 2.3 ± 1.1 log (CFU/g) respectively. B. thuringiensis (41.9%) and B. cereus sensu stricto (36.0%) were the isolated species. The majority virulence genes found were cytK-2 (80.8%), hblD (72.1%) and nheC (70.9%). The isolates were highly resistant to tetracycline (94.8%), ciprofloxacin (94.8%) and chloramphenicol (94.2%). The probability of consuming milk and attiéké contaminated with B. cereus group is 21.6% and 16.0% respectively. In total 12.6% and 18.9% of consumers reported that they contracted a foodborne illness after unheated milk and attiéké consumption respectively and the most symptoms were diarrhea and abdominal pain. The hydrothermal warm up of attiéké with a temperature greater than or equal to 90°C for at least 15 minutes reduced the concentration of B. cereus spores from 4.2 in attiéké into 1.8 ± 1.0 log (CFU/g) and D90°C was 8.5 ± 1.9 min for the quantities of attiéké varying from 150 to 450 g. The maximum duration of the milk sale at ambient temperature is 40 min while, the consumption deadline of attiéké warmed up at 90°C was 18 hours. In conclusion, milk and attiéké produced and sold in informal markets in Abidjan represents a risk for consumers’ health and B. cereus group species are one possible cause. It is recommended to heat the milk to boiling temperature and to warm up attiéké for at least 15 min at 90°C before consumption if clean milk and attiéké production cannot be assured.